2007
DOI: 10.1111/j.1365-2796.2007.01887.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a stress management program on vital exhaustion and depression in women with coronary heart disease: a randomized controlled intervention study

Abstract: Abstract. Koertge J, Janszky I, Sundin Ö , Blom M, Georgiades A, László KD, Alinaghizadeh H, Ahnve S (Karolinska Institutet, and Centre of Public Health, Stockholm County Council, Stockholm, Sweden; and Semmelweis University, Budapest, Hungary; and Karolinska Institutet at Karolinska University Hospital, Stockholm, Sweden). Effects of a stress management program on vital exhaustion and depression in women with coronary heart disease: a randomized controlled intervention study. J Intern Med 2008; 263: 281-293.O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 41 publications
0
24
0
1
Order By: Relevance
“…One study 15 found a reduction of the number of exhausted patients after a behavioral intervention, but exclusively so in persons without a history of CHD. Another study 16 showed a decrease of VE in women with CHD after a stress management training in a randomized controlled intervention study, both in the intervention group and the control group. Although these studies revealed VE changes over time, the factors contributing to these changes remained unclear.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…One study 15 found a reduction of the number of exhausted patients after a behavioral intervention, but exclusively so in persons without a history of CHD. Another study 16 showed a decrease of VE in women with CHD after a stress management training in a randomized controlled intervention study, both in the intervention group and the control group. Although these studies revealed VE changes over time, the factors contributing to these changes remained unclear.…”
Section: Discussionmentioning
confidence: 97%
“…No significant effect on VE was observed in women with CHD in the second study. 16 In addition, several studies showed sex differences in VE with scores being higher in women relative to men. 7,17,18 The protective role of positive affect (PA) in cardiovascular health is increasingly acknowledged.…”
Section: Downloaded By [Kungliga Tekniska Hogskola] At 02:19 03 Octobmentioning
confidence: 98%
“…This instrument is extensively used to evaluate treatment effects, for instance in Swedish studies on cardiac disease [30][31][32]. Responses to the 19 items were given on three-point scales (0-2), total range 0-38, high scores indicating a high degree of 'vital exhaustion'.…”
Section: Psychometric Datamentioning
confidence: 99%
“…The diagnosis of AMI was based on World Health Organization's criteria of typical enzyme patterns and chest pain and/or diagnostic electrocardiographic changes [35]. Consecutively, all eligible women below 75 years were approached and offered to participate in a cardiac rehabilitation program specifically designed for women [36]. Subsequently, all those who agreed to participate were randomly assigned to either the control (128 patients) or to the intervention group (119 patients).…”
Section: Study Populationmentioning
confidence: 99%